CBLT IN DEVELOPING LISTENING SKILLS - Umarkhujayeva, Kh.S. (SCIENCE and SOCIETY, 2026)
This article explores the role of Content-Based Language Teaching (CBLT) in developing listening skills among non-linguistic learners. It highlights how integrating authentic content with listening, speaking, and writing tasks, along with scaffolding strategies, enhances comprehension, discourse competence, and long-term retention. Despite challenge such as material selection, CBLT provides an effective framework for holistic language development and preparation for academic and professional communication.
Keywords: CBLT; listening skills; discourse competence; receptive skills; scaffolding techniques; analytical thinking